Arzneimittelinteraktionen - ihre Bedeutung für eine sichere Therapie am Beispiel der neuen Wirkstoffgruppe der Thiazolidindione (Glitazone) - Klotz, Ulrich; Sailer, Dietmar (Arzneimittelforschung, 2001)
Drug Interactions - their Impact on Safe Drug Therapy as Exemplified by the Novel Group of Thiazolidinediones (Glitazones)Troglitazone (CAS 97322-87-7), rosiglitazone (CAS 155141-29-0) and pioglita -zone (CAS 111025-46-8) represent novel agents for the treatment of diabetes mellitus. Very often such patients receive several drugs at the same time and consequently their interaction potential needs to be known, especially as troglitazone was recently withdrawn from the market partly because it inhibited and induced drug metabolism.Sometimes interactions can be extrapolated from the pharmacokinetic properties of the involved drugs. So farrosiglitazone which is metabolized mainly by the cytochrome CYP2C8 has shown no clinically relevant interactions with acarbose, metformin, glibornuride, nifedipine, oral contraceptives, warfarin or digoxin. The metabolism of pioglita-zone is mainly accomplished by CYP3A4, CYP2C8/9 and CYP1A1/2. Likewise, no interactions have been reported until now. However, it would be informative, if some interaction studies with typical CYP3A4 substrates had been performed as more than 50 % of all drugs (including pioglitazone) are metabolized by CYP3A4. Thus, at least theoretically more interactions might be expected with pioglitazone if compared to rosiglitazone, as only very few drugs are metabolized by CYP2C8.
Keywords: CAS 97322-87-7; CAS 111025-46-8; CAS 155141-29-0; Diabetes mellitus; Glitazones, drug interactions, pharmacokinetics, review; Pioglitazone; Rosiglitazone; Troglitazone